2022
DOI: 10.1021/acs.langmuir.2c02379
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Attraction: A New Mechanism of Nanoparticle Aggregation

Abstract: Solvent-induced interactions of nanoparticles in colloidal solutions can substantially affect their physicochemical and transport properties. Predicting these interactions is challenging because the natural causes of the interactions are unclear. Here, we present a comprehensive experimental and theoretical study of the coagulation stability of the surfacted magnetic colloids. The magnetite nanoparticles stabilized by erucic acid were dispersed in 19 different good solvents. The colloidal stability was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Single-nm sized NPs possess high curvature, which might affect the lateral chain packing of modifiers. Lysenko et al carried out a comprehensive study of magnetic NP coagulation in various solvents . They reported that the osmotic attraction could be a driving force for particle coagulation, where the depletion interaction between NPs could be induced by precipitant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-nm sized NPs possess high curvature, which might affect the lateral chain packing of modifiers. Lysenko et al carried out a comprehensive study of magnetic NP coagulation in various solvents . They reported that the osmotic attraction could be a driving force for particle coagulation, where the depletion interaction between NPs could be induced by precipitant.…”
Section: Resultsmentioning
confidence: 99%
“…Lysenko et al carried out a comprehensive study of magnetic NP coagulation in various solvents. 48 They reported that the osmotic attraction could be a driving force for particle coagulation, where the depletion interaction between NPs could be induced by precipitant. Particle coagulation can be induced by adding polymer NPs as depletant, 49 where the size of depletant is much smaller than the particles.…”
Section: Resultsmentioning
confidence: 99%